Portrait of the Implementation of Statistics Lectures in Islamic Religious Education: An Evaluative Study with the Countenance Stake Model - Nur Anisyah Rachmaningtyas (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
The output of statistics learning in Islamic religious education study programs still tends to need to be improved. This has an impact on the next prerequisite course, namely quantitative research methodology learning. This study aims to evaluate the statistics learning process in Islamic religious education study programs. The evaluation model used in this study is the Stake Countenance Model which consists of three evaluation steps, namely antecedent, transaction, and outcomes. The subjects of this study were 104 students who took statistics courses. The instruments used in this study were RPP observation sheets, assessment documentation sheets, and interview guidelines. This study uses a quantitative research approach supported by qualitative data. The results of the study show that (1) the lecture implementation plan in one semester of statistics courses is in the good category (90.50%), (2) the statistics learning process, both practice and theory, is in the good category (87.75%), (3) student assessment documents are in the fairly good category (71.25%), (4) overall, the lecture program in statistics courses shows that no less than 75% of students are classified as students above the minimum completion.